Addiction: From Context-Induced Hedonia to Appetite, Based on Transition of Micro-behaviors in Morphine Abstinent Tree Shrews - Duan, Ying; Shen, Fang; Gu, Tingting; Sui, Nan (Frontiers in Psychology, 2016)
Abstract Drug addiction is viewed as a maladaptive memory induced by contextual cues even in the abstinent state. However, the variations of hedonia and appetite induced by the context during the abstinence have been neglected. To distinguish the representative behaviors between hedonia and appetite, micro-behaviors in abstinent animal such as psycho-activity and drug seeking behaviors were observed in morphine conditioned place preference (CPP). To confirm the different effects of reward between drug and natural reward, a palatable food CPP paradigm was compared in current work. After a 10-day training in CPP with morphine or food, the preference was tested on day 1, 14, 28, and the changes of micro-behaviors were analyzed further. Our data showed that tree shrews treated with morphine performed more jumps on day 1 and more visits to saline paired side on day 28, which indicated a featured behavioral transition from psycho-activity to seeking behavior during drug abstinence. Meanwhile, food-conditioned animals only displayed obvious seeking behaviors in the three tests. The results suggest that the variations of micro-behaviors could imply such a transition from hedonic response to appetitive behaviors during morphine abstinence, which provided a potential behavioral basis for further neural mechanism studies.